Prosecution of pirates under international law: in Limbo - Ahmed, Md Hassan@Kyaw Hla Win; Hamid, Abdul Ghafur@Khin Maung Sein; Ali Mohamed, Ashgar Ali (LexisNexis, 2014)
Piracy has long posed a threat to the safety of maritime navigation and thus it is extremely essential to provide efficient deterrence through proper prosecution of the offenders. As far as international law is concerned, perpetrators of piracy are prosecuted under the domestic laws and before the domestic courts of State Parties. The piracy regime under the United Nations Convention on the Law of the Sea 1982 ('UNCLOS') does not stipulate any punishment and the culprits have been serving uncertain degree of punishment as sentences are varied from one jurisdiction to another. There are also some states with a lack of interest on prosecuting pirates. Therefore, this article intends to analyse the prosecution of pirates in some selected jurisdictions and suggest viable solutions to assure more appropriate trials as well as punishment for the offenders of piracy. Accordingly, it is suggested that the UNCLOS 1982 should provide some legal guidelines as to the maximum and minimum punishments for the offenders on the basis of the seriousness of the crime. In cases where a custodial state is reluctant to prosecute and punish the offenders, it should be given the option to extradite the offenders to another state which has interest in prosecution in line with the contemporary international law. When there is no state willing to prosecute and request for extradition, then the offenders should be prosecuted before the International Criminal Court ('ICC').